2005
DOI: 10.1002/cbf.1152
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal plasma adenosine deaminase, xanthine oxidase and malondialdehyde levels in pre-eclampsia

Abstract: The aim of this study was to evaluate maternal-fetal plasma adenosine deaminase, xanthine oxidase (ADA, XO) activity and malondialdehyde (MDA) levels and the relationship between them in pre-eclampsia. Maternal and umbilical cord whole blood samples were taken from 29 pre-eclamptic and 33 normal pregnants. The plasma ADA, XO activities as well as MDA levels were assayed by spectrophotometric methods. MDA levels and ADA, XO activities were found to be higher in maternal and fetal plasma in pre-eclamptics than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 25 publications
0
31
1
3
Order By: Relevance
“…MDA is a marker of lipid peroxidation in ischemic tissues [30]. Intensity of MDA staining was the same in sham and infliximab + pringle groups and high in Pringle group.…”
Section: Discussionmentioning
confidence: 86%
“…MDA is a marker of lipid peroxidation in ischemic tissues [30]. Intensity of MDA staining was the same in sham and infliximab + pringle groups and high in Pringle group.…”
Section: Discussionmentioning
confidence: 86%
“…Considering that adenosine at high concentrations could have deleterious effects, and the fact that intracellular uptake is one of the main mechanisms for controlling the extracellular level of adenosine, those results were interpreted as a compensatory response, present in preeclampsia, to address the recovery of the physiological extracellular adenosine concentration in the feto-placental circulation. Compatible with this idea, Karabulut et al [29] have shown that elevation of adenosine levels triggers a compensatory elevation of adenosine deaminase activity in the umbilical circulation. Despite this latest evidence, the causes or consequences of high adenosine levels in the feto-placental circulation during preeclampsia are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the present study, we evaluated ADA activity in maternal and fetal plasma and in placental tissue and investigated possible correlations between the severity of pre-eclampsia and ADA activity in these three compartments.…”
Section: Discussionmentioning
confidence: 99%